Efforts to Improve English Speaking Skills Using Action Learning Strategies in Class X MIA 1 MA Hidayatul Mubtadiin Sidoharjo Jati Agung Lampung Selatan - Nilna Muna Khoiriyah; Ani Latifah; Hasna Fitri Labibah (Departement of Mathematics Education, 2024)
This research aims to determine students' speaking abilities using action learning strategies in class X MIA 1 MA Hidayatul Mubtadiin Sidoharjo Jati Agung South Lampung. The type of research used is qualitative research. The data sources in the research are school principals, teachers and students. The research instruments used were observation guidelines, interview guidelines and documentation. The data analysis techniques used are data reduction, data presentation and data verification. The research results showed a significant improvement in students' English speaking skills after participating in the action-based learning intervention. Students demonstrate an increase in their ability to communicate effectively in real-life situations. First, the results of learning English, namely with action learning strategies, teachers can find out students' own learning outcomes, namely by preparing basic material for students, so that students are confident and dare to give opinions to solve problems from each material presented. And the results of learning to speak English at MA Hidayatul Mubtadiin. Second, the supporting and inhibiting factors for teachers in implementing learning action strategies at MA Hidayatul Mubtadiin are quite good, good and capable facilities and infrastructure are expected to help English teachers in implementing learning action strategies through lesson plans or RPPs, while the inhibiting factors are: Things that The biggest obstacle in the learning process is students' lack of understanding, plus limited time during the learning process and a lack of understanding of English.